2013
DOI: 10.1007/s00234-013-1155-8
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labelling MRI for assessment of cerebral perfusion in children with moyamoya disease: comparison with dynamic susceptibility contrast MRI

Abstract: INTRODUCTION:This study seeks to evaluate the diagnostic accuracy of cerebral perfusion imaging with arterial spin labelling (ASL) MR imaging in children with moyamoya disease compared to dynamic susceptibility contrast (DSC) imaging. METHODS: Ten children (7 females; age, 9.2 ± 5.4 years) with moyamoya disease underwent cerebral perfusion imaging with ASL and DSC on a 3-T MRI scanner in the same session. Cerebral perfusion images were acquired with ASL (pulsed continuous 3D ASL sequence, 32 axial slices, TR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
1
32
0
3
Order By: Relevance
“…In addition, several previous studies reported that measured CBF values were similar between ASL and SPECT and between ASL and DSC MR imaging in patients with Moyamoya disease or carotid stenosis. 24,37,38 According to these results, the sensitivity of ASL might be greater than that of SPECT for assessing cerebral perfusion during follow-up in patients with CCD and correlating the findings with the clinical course. Therefore, additional study using ASL is necessary to investigate the serial changes in CCD and their clinical importance.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, several previous studies reported that measured CBF values were similar between ASL and SPECT and between ASL and DSC MR imaging in patients with Moyamoya disease or carotid stenosis. 24,37,38 According to these results, the sensitivity of ASL might be greater than that of SPECT for assessing cerebral perfusion during follow-up in patients with CCD and correlating the findings with the clinical course. Therefore, additional study using ASL is necessary to investigate the serial changes in CCD and their clinical importance.…”
Section: Discussionmentioning
confidence: 93%
“…20 In a recent study with the use of DSC as the standard of reference in children with Moyamoya disease, it could be demonstrated that ASL-based measurements of CBF showed a similarly strong and significant correlation with DSC-based perfusion (r ϭ 0.79, P Ͻ .001), enabling the detection of impaired perfusion per cerebral vascular territory with a high diagnostic accuracy. 9 In a direct comparison of ASL and H 2 [ 15 O]-PET, one study found similar cortical perfusion values with no significant …”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 To investigate the effects of variations in blood T1 across the patient group, the blood T1 was calculated for n ϭ 11 patients from venous hematocrit levels according to the equation T1 ϭ 1/(0.83 Hct ϩ 0.28).…”
Section: 13mentioning
confidence: 99%
“…Examples where ASL has found application in the paediatric population include patients with temporal lobe epilepsy, 6 acute ischaemic stroke, 7 brain tumours, 8 sickle cell disease, 9-11 neurotuberculosis, 12 focal cortical dysplasia, 13,14 arteriovenous malformations, 15 traumatic brain injury 16 and moyamoya disease. 17 There have been several studies performed that compare perfusion measurements obtained from ASL with those from DSC, [18][19][20][21][22][23] particularly in stroke and brain tumour populations, but few have been performed in a paediatric population. 17 The purpose of this study was to make a qualitative comparison between CBF images produced by traditional DSC MRI and those produced using ASL MRI in a group of paediatric patients imaged as part of the routine investigation of a variety of neurological conditions.…”
Section: Introductionmentioning
confidence: 99%